2022
DOI: 10.3389/fimmu.2022.940009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Drug-Eluting Beads Transarterial Chemoembolization Combining Immune Checkpoint Inhibitors in Unresectable Intrahepatic Cholangiocarcinoma: A Propensity Score Matching Analysis

Abstract: PurposeTo assess the effectiveness and safety of drug-eluting beads transarterial chemoembolization plus immune checkpoint inhibitors (DEB-TACE+ICIs) versus chemotherapy (gemcitabine+cisplatin) for patients with unresectable intrahepatic cholangiocarcinoma (iCCA).Materials and MethodsThis retrospective study included unresectable iCCA patients treated with DEB-TACE+ICIs or chemotherapy between May, 2019 and August, 2021. The differences in tumor responses, progression-free survival (PFS), overall survival (OS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…In the present research, the results of univariate and multivariate analysis showed that for the treatment of ICC, the type of treatment, bilirubin level (≤ 20 / > 20 µmol/L), number of tumors (single/multiple) and number of TACE (≤ 3 / > 3) were independent prognostic factors for PFS. CA199 (≤ 37 / > 37 U/mL), ALT (≤ 35 / > 35 U/L) and number of TACE (≤ 3 / > 3) were independent prognostic factors for OS, ndings consistent with previously published literature (Sun et al 2022;Yang et al 2022). Among the factors, a high bilirubin concentration (> 20 µmol/L) and large number of tumors were risk factors for PFS.…”
Section: Safetysupporting
confidence: 90%
“…In the present research, the results of univariate and multivariate analysis showed that for the treatment of ICC, the type of treatment, bilirubin level (≤ 20 / > 20 µmol/L), number of tumors (single/multiple) and number of TACE (≤ 3 / > 3) were independent prognostic factors for PFS. CA199 (≤ 37 / > 37 U/mL), ALT (≤ 35 / > 35 U/L) and number of TACE (≤ 3 / > 3) were independent prognostic factors for OS, ndings consistent with previously published literature (Sun et al 2022;Yang et al 2022). Among the factors, a high bilirubin concentration (> 20 µmol/L) and large number of tumors were risk factors for PFS.…”
Section: Safetysupporting
confidence: 90%
“…Then, some clinical studies have shown that using 100–300 μm beads may improve efficacy and safety of TACE. Most studies of efficacy and safety of DEB-TACE in ICC using 100–300 μm beads to treat ICC patients ( Martin et al, 2022 ; Yang, et al, 2022 ). In a retrospective, single institution study conducted from 2010 to 2012, 61 participants were treated with TACE performed with 100–300 μm or 300–500 μm DEBs.…”
Section: Discussionmentioning
confidence: 99%
“…The score is rated out of 9 stars: >6 stars indicate a low risk of bias, 4-6 stars indicate a moderate risk of bias, and <4 stars indicate a high risk of bias. Out of the ten studies included [20][21][22][23][24][25][26][27][28][29] in the systematic review, three studies [24][25][26] were determined to be of good quality, and seven studies [20][21][22][23][27][28][29] were determined to be of acceptable quality. Details of the quality assessment are shown in Supplementary Table 2.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Ten cohort studies were deemed eligible and included in the descriptive analysis; of the 3,791 patients in these studies, 1,120 (29.5%) were treated with LRT + ST. ADT was performed in six articles 20,[22][23][24]27,28 , EBRT in three 25,26,29 , and ablation in one 21 (Table 1). Further details of the included literature are provided in Supplementary Table 3.…”
Section: Baseline Characteristicsmentioning
confidence: 99%